A rare case of vaginal sarcoma in pregnancy - Kujur, Avinashi; Roy, Archana; Ekka, Suma Velgin; Gupta, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Vaginal Sarcoma is an extremely rare tumour in pregnancy. Authors are presenting a case report of a pregnant woman who presented with vaginal mass and urinary retention at 32 weeks of gestational age. USG confirmed a live baby with possibility of cervical fibroid. Before further investigations for diagnosis of the mass her emergency LSCS has to be done. Histopathology and immunohistochemistry then confirmed sarcoma.